Henri Lefebvre, Space and Folklore - Rogers, Tim (Ethnologies, 2002)
AbstractThe complex spatial thinking of Henri Lefebvre and its implications for folkloristics are explored in the context of a fictitious conversation between him and the author as they walk around a small farm in southeastern British Columbia. Aspects of Lefebvre’s position are explored and illustrated using examples from this setting, such as fences and campfire pits. Lefebvre’s tripartite schema for conceptualizing space is articulated during this conversation, foregrounding the importance of the oft-occluded espace vécu (lived space). Viewing this as a dialogic, embodied, open-ended domain of space is shown to be a highly generative and potentially transformative approach to understanding space — an approach which has numerous implications for the study of cultural tradition.